Faster than normal eaudiobook Turbocharge your focus, productivity, and success with the secrets of the adhd brain. - Shankman, Peter (Penguin Audio, 2017)
A refreshingly practical and honest guide that rewrites the script on ADHD Peter Shankman is a busy guy — a media entrepreneur who runs several businesses, gives keynote speeches around the world, hosts a popular podcast, runs marathons and Iron Mans, is a licensed skydiver, dabbles in angel investing, and is loving father to his young daughter.  Simply put, he always seems to have more than 24 hours in a day. How does he do it? Peter attributes his unusually high energy level and extreme productivity to his ADHD.  In Faster Than Norma l, Shankman shares his hard-won insights and daily hacks for making ADHD a secret weapon for living a full and deeply satisfying life. Both inspiring and practical, the book presents life rules, best practices, and simple but powerful ways to: Harness your creative energy to generate and execute your ideas Direct your hyperfocus to get things done  Identify your pitfalls—and avoid them Streamline your daily routine to eliminate distractions Use apps and other tech innovations to free up your time and energy Filled with ingenious hacks and supportive self-care advice, this is the positive, practical book the ADHD community has long needed - and is also an invaluable handbook for anyone who's sick of feeling overwhelmed and wants to drive their faster-than-normal brain at maximum speed...without crashing.